Effects of chloride ions on corrosion of ductile iron and carbon steel in soil environments - Yarong Song (Nature Portfolio, 2017)
Abstract Chloride is reported to play a significant role in corrosion reactions, products and kinetics of ferrous metals. To enhance the understanding of the effects of soil environments, especially the saline soils with high levels of chloride, on the corrosion of ductile iron and carbon steel, a 3-month corrosion test was carried out by exposing ferrous metals to soils of six chloride concentrations. The surface morphology, rust compositions and corrosion kinetics were comprehensively studied by visual observation, scanning electron microscopy (SEM), X-Ray diffraction (XRD), weight loss, pit depth measurement, linear polarization and electrochemical impedance spectroscopy (EIS) measurements. It showed that chloride ions influenced the characteristics and compositions of rust layers by diverting and participating in corrosion reactions. α-FeOOH, γ-FeOOH and iron oxides were major corrosion products, while β-Fe8O8(OH)8Cl1.35 rather than β-FeOOH was formed when high chloride concentrations were provided. Chloride also suppressed the decreasing of corrosion rates, whereas increased the difficulty in the diffusion process by thickening the rust layers and transforming the rust compositions. Carbon steel is more susceptible to chloride attacks than ductile iron. The corrosion kinetics of ductile iron and carbon steel corresponded with the probabilistic and bilinear model respectively.